2015
DOI: 10.1063/1.4906761
|View full text |Cite
|
Sign up to set email alerts
|

The photorefractive characteristics of bismuth-oxide doped lithium niobate crystals

Abstract: Bismuth-doped lithium niobate (LN:Bi) crystals were grown by Czochralski method and their optical damage resistance, photorefraction, absorption spectra, and defect energy levels were investigated. The experimental results indicate that the photorefractive properties of LN:Bi were enhanced as compared with congruent one, the photorefractive response time was greatly shortened, the photorefractive sensitivity was increased, and the diffraction efficiency of near-stoichiometric LN:Bi (SLN:Bi) reached 31.72% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The micro-mechanism of this phenomenon was considered as that Mg 2+ dopants push Nb Li 5+ ions and photorefractive impurities from Li-sites to Nb-sites, which will cause these ions lose their function as photorefractive centers, therefore the optical damage resistance of LN:Mg is greatly improved. It was reported that the damage threshold of CLN and LN:Bi 1.0 is lower than 40 W/cm 2 and that of LN:Mg 5.0 is around 5 × 10 5 W/cm 2 under the same experimental conditions of this work 17 18 . Figure 2 shows that the optical damage threshold of LN:Bi,Mg 5.0 and LN:Bi,Mg 6.0 both reach 5.8 × 10 6 W/cm 2 .…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The micro-mechanism of this phenomenon was considered as that Mg 2+ dopants push Nb Li 5+ ions and photorefractive impurities from Li-sites to Nb-sites, which will cause these ions lose their function as photorefractive centers, therefore the optical damage resistance of LN:Mg is greatly improved. It was reported that the damage threshold of CLN and LN:Bi 1.0 is lower than 40 W/cm 2 and that of LN:Mg 5.0 is around 5 × 10 5 W/cm 2 under the same experimental conditions of this work 17 18 . Figure 2 shows that the optical damage threshold of LN:Bi,Mg 5.0 and LN:Bi,Mg 6.0 both reach 5.8 × 10 6 W/cm 2 .…”
Section: Resultssupporting
confidence: 64%
“…The absorption spectrum of LN is sensitive to crystal composition and defects, and as we known that Bi dopants can introduced new absorption peaks into LN crystals 18 . The UV-visible transmission spectra of LN:Bi,Mg crystals are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] As we know, the photorefractive properties of LiNbO3 can be improved by doping with Fe 3+/2+ , Mn 3+∕2+ , Cu 2+∕+ , or Bi 3+∕2+ ions. [4][5][6][7][8][9] These materials are promising candidates for holographic storage applications. For example, bismuth (Bi) and magnesium (Mg) co-doped LiNbO3 (LN:Bi,Mg) crystals can be used in the dynamic holographic display.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bismuth (Bi) and magnesium (Mg) co-doped LiNbO3 (LN:Bi,Mg) crystals can be used in the dynamic holographic display. 5,6 While, molybdenum-doped LiNbO3 (LN:Mo) is the only possible one for holographic storage from the ultraviolet to the visible with considerably shorter response time. 10,11 However, there are still not enough accurate and detailed knowledge about LN defects in experiments.…”
Section: Introductionmentioning
confidence: 99%